Perancangan Guitar Tuning Berbasis Web - I Nyoman Dheva Surya; Cokorda Pramartha; Agus Muliantara (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
Guitar tuning is a crucial step in preparing for playing, ensuring accurate sound production. In response to this need, our research led to the development of a web-based application dedicated to facilitating precise and straightforward guitar tuning. Leveraging web technology, this application offers users practical tuning experience without the need for additional software installation. By implementing comprehensive tuning features and employing the Fast Fourier Transform (FFT) method, our application guarantees accuracy in detecting and analyzing the spectrum of incoming sound vibrations. This technological approach ensures that users can confidently tune their guitars, avoiding mistuned strings. The decision to create a web-based app aims to optimize device space utilization, as it only requires a standard browser, readily available on all operating systems. In addition to tuning functionality, the application enriches the user experience by providing a collection of guitar chords for each note. This feature enables users to practice and play songs with adjustable transposition and speed. To assess the application's functionality and reliability, we conducted 100 trials using the BlackBox method, focusing on tuning the six guitar strings (e-b-g-d-a-e). The results demonstrated a remarkable 99% accuracy, affirming the system's effectiveness in facilitating precise guitar tuning. In conclusion, our research yields a practical, intuitive, and highly effective web application for users to tune their guitars with confidence and ease.